Introduction Situation Background Assessment Recommendation (ISBAR) Checklist to Improve Nurses’ Handover Quality - Yulianti, Lena; Putra, Kuswantoro Rusca; Lilik Supriati; Utami, Yulian Wiji; Aat Djanatunisah; Winda Yuniarsih (Babali Publisher, 2025)
Background: Patient transfer between hospital units, especially from the Emergency Department (ED) to the High Care Unit-Intensive Care Unit (HCU-ICU), carries a high risk of adverse events due to communication failures during handover. The Introduction, Situation, Background, Assessment, Recommendation (ISBAR) checklist is a structured communication tool designed to enhance handover quality but is underutilized in written patient transfer. This study aimed to evaluate the effectiveness of the ISBAR checklist in improving the quality of nurse handovers during ED to HCU-ICU patient transfers. Method: A pre-experimental study with a one-group pre-posttest design was conducted, in which ED nurses used the ISBAR checklist during patient handovers. Forty HCU-ICU nurses assessed the quality of the ED nurse handovers using the Handover Evaluation Scale (HES) questionnaire. A paired sample t-test was used to analyze the differences in handover quality before and after implementation. Result: The ISBAR checklist significantly improved nurses’ handover quality, with a p-value of 0.000 (p < 0,05). The effectiveness of the ISBAR checklist was analyzed using an N-gain score, resulting in a moderate improvement level of 0.34 (0.3 ≤ g ≥ 0.7). Conclusion: The ISBAR checklist is an effective tool for improving nurse handover quality in patient transfers. Hospitals should adopt ISBAR as a standardized handover protocol to enhance patient safety and continuity of care and establish a minimally interruptive environment during handover. Further research should explore long-term implementation and integration into electronic health records.